Lapatinib plus transtuzumab for HER-2 positiva metastatic breast cancer: Experience of use - C. García-Muñoz; S. Cortijo-Cascajares; I. Cañamares-Orbis; M. P. Goyache-Goñi; J. M. Ferrari-Piquero (Elsevier, 2014)
Abstract: Objective: To describe the outcomes produced by concomitant use of HER2-receptor inhibitors Lapatinib and Trastuzumab for the treatment of HER 2-positive metastatic breast cancer. Method: Retrospective observational study. Patients treated with Trastuzumab and Lapatinib between January of 2010 and May of 2012 were selected. Demographical and clinical data were gathered. Results: 23 patients with metastatic breast cancer (mean age 59.3 ± 13.3 years) were included. All of them had received an average of 5 treatment lines with at least one of them including Trastuzumab. The median progression-free survival rate with combined Lapatinib + Trastuzumab, with or without associated chemotherapy was 7 months (95% CI: 2.78-11.21) and 3 months for the patients only receiving Lapatinib and Trastuzumab. Seven patients experienced adverse events and in four patients the treatment was stopped due to toxicity. Conclusions: The treatment with HER2-receptor inhibitors in our patients resulted in progression-free survival rates similar to those published in clinical trials with patients receiving Lapatinib + Trastuzumab not combined with any other anti-cancer therapy, with good treatment tolerability.